Label‐Free and Continuous‐Flow Ferrohydrodynamic Separation of HeLa Cells and Blood Cells in Biocompatible Ferrofluids. (7th December 2015) - Zhao, Wujun; Zhu, Taotao; Cheng, Rui; Liu, Yufei; He, Jian; Qiu, Hong; Wang, Lianchun; Nagy, Tamas; Querec, Troy D.; Unger, Elizabeth R.; Mao, Leidong
Abstract : In this study, a label‐free, low‐cost, and fast ferrohydrodynamic cell separation scheme is demonstrated using HeLa cells (an epithelial cell line) and red blood cells. The separation is based on cell size difference, and conducted in a custom‐made biocompatible ferrofluid that retains the viability of cells during and after the assay for downstream analysis. The scheme offers moderate‐throughput (≈10 6 cells h −1 for a single channel device) and extremely high recovery rate (>99%) without the use of any label. It is envisioned that this separation scheme will have clinical applications in settings where rapid cell enrichment and removal of contaminating blood will improve efficiency of screening and diagnosis such as cervical cancer screening based on mixed populations in exfoliated samples. Abstract : A label‐free, low‐cost, and fast method in biocompatible ferrofluids is developed to ferrohydrodynamically separate HeLa cells and red blood cells based on their size difference. It offers moderate‐throughput (≈10 6 cells h −1 for a single channel device) and extremely high recovery rate (>99 %) for the enrichment of HeLa cells from blood.